Pyk2/MCU Pathway as a New Target for Reversing Atherosclerosis - Zhang, Yingzhen; Yang, Xiaoli; Li, Zhongzhong; Bu, Kailin; Li, Tong; Ma, Zhizhao; Wang, Binbin; Ma, Lina; Lu, Honglin; Zhang, Kun; Liu, Luji; Zhao, Yanying; et al. (Frontiers in Cell and Developmental Biology, 2021)
Objective: Multiple mechanisms including vascular endothelial cells damage have a critical role in the formation and development of atherosclerosis (AS), but the specific molecular mechanisms are not exactly clarified. This study aims to determine the possible roles of proline-rich tyrosine kinase 2 (Pyk2)/mitochondrial calcium uniporter (MCU) pathway in AS mouse model and H2O2-induced endothelial cells damage model and explore its possible mechanisms. Approach and Results: AS mouse model was established using apolipoprotein E-knockout (ApoE−/−) mice that were fed with high fat diet. It was very interesting to find that Pyk2/MCU expression was significantly increased in the artery wall of atherosclerotic mice and human umbilical vein endothelial cells (HUVECs) attacked by H2O2. In addition, down-regulation of Pyk2 by short hairpin RNA (shRNA) protected HUVECs from H2O2 insult. Furthermore, treatment with the rosuvastatin on AS mouse model and H2O2-induced HUVECs injury model showed a protective effect against AS by inhibiting Pyk2/MCU pathway, which maintained calcium balance, prevented the mitochondrial damage, reactive oxygen species (ROS) production, and eventually inhibited cell apoptosis. Conclusions: Our results provide important insight into the initiation of Pyk2/MCU pathway involved in AS related ECs damage, which may be a new promising target for atherosclerosis intervention.